Studies toward the Second-Generation Synthesis of Epolactaene: Highly Stereoselective Construction of the Epoxy-γ-Lactam Moiety - Tajima, Kouta; Umehara, Yoshifumi; Kobayashi, Kenichi; Kogen, Hiroshi (Synlett, 2014)
Highly stereoselective synthesis of the epoxy-γ-lactam moiety toward the second-generation total synthesis of epolactaene was achieved via an E-selective Horner–Wadsworth–Emmons reaction using our new reagent and diastereoselective epoxidation of an allyl diol with VO(acac)2 and TBHP.
Keywords: epolactaene; Horner–Wadsworth–Emmons reaction; (E)-α-bromoacrylate; stereoselective synthesis; epoxidation; epoxy-γ-lactam